Reaching the Unreachable: Strategies for HCV Eradication in Patients With Refractory Opioid Addiction—A Real-world Experience. (17th June 2021) - Sandmann, Lisa; Deppe, Julian; Beier, Christoph; Ohlendorf, Valerie; Schneider, Julia; Wedemeyer, Heiner; Wedegärtner, Felix; Cornberg, Markus; Maasoumy, Benjamin
Abstract: To achieve global hepatitis C virus (HCV) eradication, barriers prohibiting treatment access need to be overcome. We established a strategy to initiate antiviral therapy in patients with severe, refractory heroin addiction. All patients achieved sustained virological response. Outreach programs of hepatologists might be a reasonable way to overcome barriers to HCV treatment.